PEMBUATAN WESTAFEL MINI OTOMATIS DENGAN MEMANFAATKAN KEMBALI AIR KONDENSASI AC - Rina Rina (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2021)
The current condition of Covid-19 requires washing hands with more intensity so that it requires more water. While the water from the condensation of the Air-Conditioner is wasted. So from that an automatic mini sink was made with the water source taken from the condensation of the Air-Conditioner. This sink is designed to make it easier to wash your hands without the need to touch the water tap and the soap. Automatic mini westafel is assembled with IR sensor, 1 channel 5 V relay, IC 7805, 12 V water pump, 12 V mini vacuum pump, 12 V 30 A 4 pin relay, and a 12 V adapter which functions as an automatic working system on water faucets and soap. Air-Conditioner condensation water with a power of 1 PK produces 8.8 L / day (8 hours of work) can be used to wash hands 35 times if once washing water is used 0.25 L. The construction of the automatic mini sink frame is designed using PVC material ¾ '' with the aim of making it easier for water to flow through the pipe frame. Keywords: Design, automatic mini sink, Air-Conditioner condensation